Simple power supply for power load controlled isoelectric focusing - Duša, Filip; Slais, Karel (Electrophoresis, 2014)
The power supply for IEF based on features of the Cockcroft-Walton voltage multiplier (CW VM) is described in this work. The article describes a design of the IEF power supply, its electric characteristics, and testing by IEF analysis. A circuit diagram of the power supply included two opposite charged branches (each consisting of four voltage doublers). The designed CW VM was powered by 230 V/50 Hz alternate current and it generated up to 5 kV and 90 mW at the output. Voltage and current characteristics of the power supply were measured by known load resistances in the range from 10 kΩ to 1 GΩ, which is a common resistance range for IEF strip geometry. Further, the power supply was tested by a separation of a model mixture of colored pI markers using a 175 × 3 × 0.5 mm focusing bed. Automatically limited power load enabled analysis of samples without previous optimization of the focusing voltage or electric current time courses according to sample composition. Moreover, the developed power supply did not produce any intrinsic heat and was easy to set up with cheap and commonly available parts.
Keywords: elektřina; Electric Power Supplies; design vybavení; isoelektrická fokusace; Power supply; Isoelectric Focusing; Voltage multiplier; Equipment Design; zdroje elektrické energie; Isoelectric focusing; Electricity